2014
DOI: 10.1038/ncomms4646
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of exciton transport in ordered and disordered molecular solids

Abstract: Transport of nanoscale energy in the form of excitons is at the core of photosynthesis and the operation of a wide range of nanostructured optoelectronic devices such as solar cells, lightemitting diodes and excitonic transistors. Of particular importance is the relationship between exciton transport and nanoscale disorder, the defining characteristic of molecular and nanostructured materials. Here we report a spatial, temporal and spectral visualization of exciton transport in molecular crystals and disordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
398
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(420 citation statements)
references
References 36 publications
(50 reference statements)
19
398
0
3
Order By: Relevance
“…1 and 2 over the full range of accessible delays indicates that carrier transport is within the diffusive regime. Carrier trapping, which would lead to subdiffusive behavior, 44 therefore has a negligible influence on the carrier kinetics within the first nanosecond after excitation. This is in agreement with studies of CH 3 NH 3 PbI 3 thin films using transient absorption microscopy, 23 in which a diffusive model accounted for the spatiotemporal carrier occupation over a 3 ns time interval after excitation.…”
Section: −1 S Is Plotted Versus 8πmentioning
confidence: 99%
“…1 and 2 over the full range of accessible delays indicates that carrier transport is within the diffusive regime. Carrier trapping, which would lead to subdiffusive behavior, 44 therefore has a negligible influence on the carrier kinetics within the first nanosecond after excitation. This is in agreement with studies of CH 3 NH 3 PbI 3 thin films using transient absorption microscopy, 23 in which a diffusive model accounted for the spatiotemporal carrier occupation over a 3 ns time interval after excitation.…”
Section: −1 S Is Plotted Versus 8πmentioning
confidence: 99%
“…[80][81][82][83] As shown in Fig. 4, the spatial spread of the signal at each delay time can be fitted with a Gaussian function parameterized by variance s. The exciton diffusion length L at delay time t is then related to the exciton density characterized by variance s,…”
Section: (5) Direct Visualization Of Tetmentioning
confidence: 99%
“…80 They also demonstrated that the mechanism of exciton transport depends strongly on the nanoscale morphology. Note that these measurements were performed at long timescales, up to 7 ms with a temporal resolution of 100 ns.…”
mentioning
confidence: 99%
“…IXs were realized in wide single quantum wells (WSQW) [1][2][3][4] and in coupled quantum wells (CQW) [5][6][7][8] [2-4, 6, 7]. Their long lifetimes allow IXs to travel over large distances before recombination, providing the opportunity to study exciton transport by optical imaging [9][10][11][12][13][14][15] and explore excitonic circuit devices based on exciton transport, see [16] and references therein.Materials with a high IX binding energy allow extending the operation of the excitonic devices to high temperatures [17][18][19]. Furthermore, such materials can allow the realization of high-temperature coherent states of IXs [19].…”
mentioning
confidence: 99%
“…Materials with a high IX binding energy allow extending the operation of the excitonic devices to high temperatures [17][18][19]. Furthermore, such materials can allow the realization of high-temperature coherent states of IXs [19].…”
mentioning
confidence: 99%